An insight into the in vivo imaging potential of curcumin analogues as fluorescence probes - Yu Liu; Chuang Zhang; Hao Pan; Li Li; Yanjie Yu; Bingmi Liu (Elsevier, 2021)
Curcumin and its derivatives have good electrical and optical properties due to the highly symmetric structure of delocalized π electrons. Apart from that, curcumin and its derivatives can interact with numerous molecular targets, thereby exerting less side effects on human body. The fluorescence emission wavelength and fluorescence intensity of curcumin can be enhanced by modifying its π-conjugated system and ß-diketone structure. Some curcumin-based fluorescent probes have been utilized to detect soluble/insoluble amyloid-ß protein, intracranial reactive oxygen species, cysteine, cancer cells, etc. Based on the binding characteristics of curcumin-based fluorescent probes with various target molecules, the factors affecting the fluorescence intensity and emission wavelength of the probes are analyzed, in order to obtain a curcumin probe with higher sensitivity and selectivity. Such an approach will be greatly applicable to in vivo fluorescence imaging.